A Phase II Randomized Clinical Trial and Mechanistic Studies Using Improved Probiotics to Prevent Oral Mucositis Induced by Concurrent Radiotherapy and Chemotherapy in Nasopharyngeal Carcinoma - Xia, Chaofei; Jiang, Chunling; Li, Wenyu; Wei, Jing; Hong, Hu; Li, Jingao; Feng, Liu; Wei, Hong; Xin, Hongbo; Chen, Tingtao (Frontiers in Immunology, 2021)
Earlier evidence has proven that probiotic supplements can reduce concurrent chemoradiotherapy (CCRT) -induced oral mucositis (OM) in nasopharyngeal cancer (NPC). We enrolled 85 patients with locally advanced NPC who were undergoing CCRT. The patients were randomized (1:1) to receive either a probiotic mixture or placebo. The incidence of severe OM (grade 3 or higher) was the primary endpoint to document. To investigate the protective effects and mechanism of probiotic combination treatment on OM induced by radiotherapy and chemotherapy, we randomly divided rats into control (C) group, model (M) group and probiotic (P) group. After treatment, samples from the tongue, blood, and fecal and proximal colon tissues on various days (7th, 14th and 21st day) were collected and tested for inflammation response, cell apoptosis, intestinal permeability, and intestinal microbial changes. We found that patients taking the probiotic combination showed significantly reduced OM. The incidences for grade 0, 1, 2, 3 and 4 OM in the placebo group and the probiotic combination group were 0%, 14.7%, 38.2%, 32.4%, and 14.7% and 13.9%, 36.1%, 25%, 22.2%, and 2.8%, respectively. Furthermore, patients in the probiotic combination group showed lower reduction rate in CD3+ T cells (75.5% vs 81%, P < 0.01), CD4+ T cells (64.53% vs 79.53%, P < 0.01), and CD8+ T cells (75.59% vs 62.36%, P < 0.01) compared with the placebo group. In the rat model, the probiotic combination could ameliorate the severity of OM, decrease the inflammation response, cell apoptosis, intestinal permeability, and restore the structure of gut microbiota to normal. In conclusion, the modified probiotic combination significantly reduces the severity of OM through enhancing the immune response of NPC patients and modifying the structure of gut microbiota.